The Medicinal Chemistry of Caffeine - Faudone, Giuseppe; Arifi, Silvia; Merk, Daniel (Journal of medicinal chemistry, 2021)
The purine alkaloid caffeine is the most widely consumed psychostimulant drug in the world and has multiple beneficial pharmacological activities, for example, in neurodegenerative diseases. However, despite being an extensively studied bioactive natural product, the mechanistic understanding of caffeine’s pharmacological effects is incomplete. While several molecular targets of caffeine such as adenosine receptors and phosphodiesterases have been known for decades and inspired numerous medicinal chemistry programs, new protein interactions of the xanthine are continuously discovered providing potentially improved pharmacological understanding and a molecular basis for future medicinal chemistry. In this Perspective, we gather knowledge on the confirmed protein interactions, structure activity relationship, and chemical biology of caffeine on well-known and upcoming targets. The diversity of caffeine’s molecular activities on receptors and enzymes, many of which are abundant in the CNS, indicates a complex interplay of several mechanisms contributing to neuroprotective effects and highlights new targets as attractive subjects for drug discovery.